STUDI KELAYAKAN DAN MAGANG USAHA PADA BADAN USAHA MILIK DESA (BUMDESA) KUTA SEJAHTERA, KABUPATEN SUMBA TIMUR - Yulita Milla Pakereng; Alliny N. R. Hutar; Lusianus H. S. Kelen; Melkianus Radja; Yohanis Ndawa R. Humba; Erastus Nggaba K. Limu; Dewi C. Suryani; Merlan R. R. Kudji; Anggreni M. Mbakundima (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Kristen Duta Wacana, 2022)
Community Service (PkM in Bahasa) carried out in the form of a feasibility study on the business of the Kuta Sejahtera Village Owned Enterprise (BUMDesa in Bahasa). This BUMDesa is located in Kuta Village, Kanatang District, East Sumba Regency, East Nusa Tenggara Province. After the feasibility study is carried out, PkM activities are continued with internships at the BUMDesa. Feasibility studies are carried out to assess businesses based on business management aspects. The internship is carried out by providing assistance to the BUMDesa of Kuta Sejahtera. The method used is a business feasibility study at BUMDesa followed by internship activities. This activity was carried out during September 2019 to January 2020. This PkM is the result of collaboration between lecturers, especially in the Management study program, students and administrators of BUMDesa Kuta Sejahtera. The results of the PkM show that based on the feasibility study found four problems according to aspects of market and marketing, engineering and technology, human resource management, and finance. Then internship was carried out to solve these problems (except the financial aspect because it was out of control), in the form of promotion and training with 100% achievement and visits to the community 73.8%.